Analysis of the Prevalence of Types of Traumatic Dental Injuries in Young Children in Lahore. - Irsam Haider, Palwasha Babar, Mariam Warda, Saqib Naeem, Rana Muhammad Ahmed, Imza Batool, Ifra Tufail (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To analyze the prevalence of type of dental traumatic injuries in young children in Lahore, Pakistan. Method: A descriptive cross-sectional study was conducted at a Co-Education school named the Ali Public School of Raiwind over a period of one month. The sample of total 280 students were used in this study. The data for all students were collected on type of dental traumatic injuries, age and gender. This data was analyzed using SPSS version 23.0. Results: The most frequent TDI involved is Type-I (58.9%) having age group 11–13 years (63.3%) with males (62%) predominance. The result of that study reveals that Type-I fracture of anterior teeth was most common in males who were more vulnerably subjected to traumatic dental injuries than females. Conclusion: There should be cautionary measures taken to avoid dental traumatic accidents that most frequently occur at home and on the roads. Keywords: Traumatic Dental Injuries, Enamel fracture